Conductivity Characterization of Insulation and Its Effects on the Calculation of the Electric Field Distribution in HVDC Cables. (17th February 2021) - Liu, Shili; Wei, Wei; Liu, Tao; Hui, Zhaoyu; Hang, Yuhua; Zheng, Huan; Suo, Changyou; Li, Zhonghua
Abstract : The calculation of an electric field distribution provides the basis for the structural design of the insulation, and an accurate characterization of conductivity as a function of temperature and electric field forms an important basis for the simulation of the electric field distribution in HVDC (high-voltage direct current) cables. However, the conductivity functions that describe the insulating materials used for HVDC cables in different studies are different, and very little has been reported regarding how to choose the most accurate function. In this work, the conductivity of insulating materials used for HVDC cables is characterized, and the effects of the conductivity characterization on the simulation of the electric field in HVDC cables are studied. First, eight common conductivity functions are compared qualitatively. Then, the conductivities of XLPE for different temperatures and electric fields are measured, and a data fitting technique is used to analyze the coincidence degree between different functions and the test results. Finally, the steady-state electric field distributions of HVDC cables for different temperature gradients are simulated in COMSOL Multiphysics. The results show that the sum of the square of the relative errors of the fitting when using the original functions is larger than that achieved when using the logarithmic form of the functions. The deviations in the electric field caused by taking the logarithm of different functions are smaller.